Demographic, medical, and financial statistics from the Jaffna Jaipur Centre for Disability Rehabilitation (JJCDR) database, 1987-2018: a prosthetics, orthotics, and mobility clinic in northern Sri Lanka - Michael, B.; Barnes, S.; Hettiaratchy, S.; Clasper, J.C.; Ahilakumar, K.; Sathiadas, M.G.; Ganeshamoorthy, J. (International Society of Global Health (ISoGH), 2023)
When dealing in global health, it is crucial to have a comprehensive understanding of community demographics and needs. From 1983-2009, a 26-year ethnic civil conflict devastated Sri Lanka, disproportionately affecting people living in the north and creating a large amputee population. Here, we use routinely collected prosthetic and orthotic data to investigate the composition of the amputee community in northern Sri Lanka.
Keywords: Prosthetics; Orthotics; Amputee; Database; Jaffna; Sri Lanka